If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) = 5(3x + -2) Reorder the terms: 3(2 + x) = 5(3x + -2) (2 * 3 + x * 3) = 5(3x + -2) (6 + 3x) = 5(3x + -2) Reorder the terms: 6 + 3x = 5(-2 + 3x) 6 + 3x = (-2 * 5 + 3x * 5) 6 + 3x = (-10 + 15x) Solving 6 + 3x = -10 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 6 + 3x + -15x = -10 + 15x + -15x Combine like terms: 3x + -15x = -12x 6 + -12x = -10 + 15x + -15x Combine like terms: 15x + -15x = 0 6 + -12x = -10 + 0 6 + -12x = -10 Add '-6' to each side of the equation. 6 + -6 + -12x = -10 + -6 Combine like terms: 6 + -6 = 0 0 + -12x = -10 + -6 -12x = -10 + -6 Combine like terms: -10 + -6 = -16 -12x = -16 Divide each side by '-12'. x = 1.333333333 Simplifying x = 1.333333333
| y=x^4-2x^3-3x^2 | | y=80x-5x^2+2 | | 24x+x^2=-1 | | ln(x/(x-9)) | | 3x+ky=25 | | (2x+4)2=25 | | (8x-5)+1=9(x+5) | | 31x^2+5=0 | | x+-7=-6 | | [8x-5]+1=9[x+5] | | ae-yd=y*y | | (-3x-6)(x-1)=0 | | a+0+y+d+e=d(0) | | -5x(5x-5)= | | x+(-7)=-15 | | 5(x-3)-2(x+4)=(x-3)+4(x-1) | | a^4-a^2+5=0 | | 3(x+8)=38-4x | | cos3y=1/2 | | 3x^2+41x-170=0 | | X-(2x+5)=-2(x+4)+19 | | -(2x+5)=2(x+4)+19 | | 60x/120x | | 4(x+4)=2(x+20) | | -8(3y+5)+y=-1 | | 25x+20=5x+40 | | 6x+18=-10 | | 2(-2y+5)-y=-5 | | 3(1.8+-0.4y)-y=8 | | 3y+25=2y+50 | | logy=alogx+b | | 9+-4y=9-4y |